Clinical outcomes of patients with advanced gastrointestinal stromal tumors: Safety and efficacy in a worldwide treatment‐use trial of sunitinib. Issue 9 (13th January 2015) - Reichardt, Peter; Kang, Yoon‐Koo; Rutkowski, Piotr; Schuette, Jochen; Rosen, Lee S.; Seddon, Beatrice; Yalcin, Suayib; Gelderblom, Hans; Williams, Charles C.; Fumagalli, Elena; Biasco, Guido; Hurwitz, Herbert I.; et al.
Abstract : BACKGROUND: The objectives of this study were to provide sunitinib to patients with gastrointestinal stromal tumor (GIST) who were otherwise unable to obtain it and to collect broad safety and efficacy data from a large population of patients with advanced GIST after imatinib failure. (ClinicalTrials.gov identifier NCT00094029). METHODS: Imatinibresistant/ intolerant patients with advanced GIST received sunitinib on an initial dosing schedule of 50 mg daily in 6‐week cycles (4 weeks on treatment, 2 weeks off treatment). Tumor assessment frequency was according to local practice, and response was assessed by investigators according to Response Evaluation Criteria in Solid Tumors version 1.0. Overall survival (OS) and safety were assessed regularly. Post hoc analyses evaluated different patterns of treatment management. RESULTS: At final data cutoff, 1124 patients comprised the intent‐to‐treat population, and 15% of these patients had a baseline Eastern Cooperative Oncology Group performance status ≥2. The median treatment duration was 7.0 months. The median time to tumor progression was 8.3 months (95% confidence interval [CI], 8.0‐9.4 months), the median OS was 16.6 months (95% CI, 14.9‐18.0 months), and 36% of patients were alive at the time of analysis. Patients for whom the initial dosing schedule was modified exhibited longer median OS (23.5 months) than those who were treated strictly according to the initial dosing schedule (11.1 months). The most common treatment‐related grade 3 and 4 adverse events were hand‐foot syndrome (11%), fatigue (9%), neutropenia (8%), hypertension (7%), and thrombocytopenia (6%). Treatment‐related adverse events associated with cardiac function (eg, congestive heart failure and myocardial infarction) were reported at frequencies of ≤1% each. CONCLUSIONS: This treatment‐use study confirms the long‐term safety and efficacy of sunitinib in a large international population of patients with advanced GIST after imatinib failure. Cancer 2015;121:1405–1413. © 2015 American Cancer Society . Abstract : Final results from a worldwide treatment‐use study of sunitinib in gastrointestinal stromal tumor (GIST) add to the existing body of evidence supporting the long‐term safety and efficacy of sunitinib in an international population of patients with advanced GIST after failure on first‐line imatinib who were ineligible for other sunitinib clinical trials. These data expand results reported in the more restricted and selected population of patients accrued to the phase 3 study of sunitinib in GIST.